Algorithmic Ecology: A Framework for Achieving Carbon-Neutrality in Global Data Infrastructure - Subhan Khan; Mohammed Bakhtawar Ahmed (International Journal of Sustainability, 2026)
The exponential growth of digital infrastructure has positioned data centers as critical enablers of the global digital economy, yet their environmental impact has become a paramount concern. Data centers consumed approximately 205 TWh globally in 2018, representing about 1% of global power usage with a steady 6% growth trend. This review synthesizes current literature on green algorithms and sustainable data center technologies, examining the intersection of artificial intelligence, machine learning optimization, renewable energy integration, and innovative cooling systems. The paper analyzes five key domains: energy-efficient algorithms, renewable energy utilization, advanced cooling systems, virtualization technologies, and carbon-aware computing. Reinforcement learning and deep reinforcement learning have shown significant potential for enhancing energy efficiency in data centers. In addition, the use of renewable energy sources, such as wind power, contributes to reducing greenhouse gas emissions by decreasing dependence on carbon-intensive fuels. Our findings reveal that sustainable data centers require multi-faceted approaches combining algorithmic optimization with infrastructure innovation. The significant empirical evidence could indicate that operational measures and increased use of renewable electricity may well demonstrate that GHG emissions could be reduced over 2020 levels by up to 70%, though achieving net-zero emissions appears to suggest that comprehensive strategies across the entire value chain remain critical. This research provides undergraduate scholars with foundational knowledge of green computing principles and emerging sustainability technologies that will define the future of data center operations.
Keywords: Machine Learning Optimization; Renewable energy; carbon footprint; energy efficiency; green algorithms; sustainable data centers